MODEL MATEMATIS UNTUK MODIFIKASI SODIUM LIGNO SULFONAT MENGGUNAKAN OLEYL AMIN DAN FORMALDEHID - , Nurlinda Ayu Triwuri ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Sodium ligno sulfonat is one of the surfactant which has the function to reduce the interfacial tension of oil and water. Sodium ligno sulfonate used in the method of enhanced oil recovery (EOR) to enhance the yield of petroleum in refinery. Sodium ligno sulfonate is from lignin which reacted with sodium bisulfate which known as sulfonation process. But becouse of the content of sodium bisulfate can reduce the performance of ligno sulfonate. To boost the performance of modified SLS by adding the oleyl amine and formaldehyde known as amino alkylation. The purpose of this research is to study the process of amino alkylation and its effect toward the quality of amin lignosulfonate. The amino alkylation process was done by applying the variations the volume of oleyl amine (1/5, 2/5, 3/5, 4/5), the speed of agitation (200 rpm, 300 rpm, 400 rpm, 500 rpm) and the reaction time are (1, 2, 3 and 4 jam). The sample was taken every hour, and being analyzed by using spectrophotometer with the wavelength of 244 nm to know the remaining concentration of oleyl amine. The data tabulation with mathematic model can be simulated using application software namely MATLAB, will be obtain the mass transfer coefficient (Kca), Reaction Rate constant (K) and distribution coefficient (Kd)